Amoxicillin diminishes the thickness of the enamel matrix that is deposited during the secretory stage in rats - Souza, Juliana Feltrin de; Gramasco, Marina [UNESP]; Jeremias, Fabiano [UNESP]; Santos-Pinto, Lourdes [UNESP]; Giovanini, Allan Fernando; Cerri, Paulo Sérgio [UNESP]; Cordeiro, Rita de Cássia Loiola [UNESP] (Wiley-Blackwell, 2015)
The use of amoxicillin during early childhood has been associated with molar incisor hypomineralization. The objective of this study was to determine whether the use of amoxicillin interferes with enamel development, during secretion and early mineralization stages. Fifteen pregnant rats were randomly assigned to three groups that received physiological solution (sham group), 100 mg/kg/day amoxicillin (A100G), and 500 mg/kg/day amoxicillin (A500G). After birth, the pups in each group received the same treatment until post-natal day 7 or 12. The upper first molars were analyzed histomorphometrical and immunostaining with amelogenin on day 7, and MMP-20 on day 12 was performed using a semiquantitative method (H-score). At 7 days, several vacuolar structures were observed in the ameloblasts in the A100G and A500G groups. A significant reduction of the enamel thickness (P < 0.001) was found in amoxicillin-treated rats compared with the sham group. Significant differences were not observed in enamel thickness (P > 0.05) between the groups of 12-day-old rats. Moreover, significant differences were not observed in the number of amelogenin- and MMP-20-immunolabeled ameloblasts (P > 0.05) between groups. The present results suggest that amoxicillin interferes with the initial stages of amelogenesis by causing structural changes in the ameloblasts and a reduction of the enamel matrix.